2016
DOI: 10.1007/s00484-016-1274-0
|View full text |Cite
|
Sign up to set email alerts
|

Microclimatic effects of planted hydroponic structures in urban environment: measurements and simulations

Abstract: The objectives of this effort was to study the effect of vertical (green wall) and horizontal (pergola) green structures on the microclimate conditions of the building surroundings and estimate the thermal perception and heat stress conditions near the two structures. The experimental data were used to validate the results simulated by the recent version (V4.0 preview III) of ENVI-met software which was used to simulate the effect of different design parameters of a pergola and a green façade on microclimate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…Apart from the southern exposure unfavorable for plants, which appeared in the design concept, three other locations of the green wall and three additional scenarios of introducing the other biophilic elements have been taken into account. The final results are comparable to the low values obtained in referenced model carried out at Kostakii Campus in Arta, which have been positively verified during the field tests [26,27].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Apart from the southern exposure unfavorable for plants, which appeared in the design concept, three other locations of the green wall and three additional scenarios of introducing the other biophilic elements have been taken into account. The final results are comparable to the low values obtained in referenced model carried out at Kostakii Campus in Arta, which have been positively verified during the field tests [26,27].…”
Section: Discussionsupporting
confidence: 83%
“…Another experiment carried out in the same atrium included both pergola and hydroponic green walls. Also in this case, high compliance of the predicted and obtained effects was confirmed [27]. Both reference examples point to the usefulness of the ENVI-met (V4) software as a useful tool for assessing atrium development variants at the design stage.…”
Section: Introductionsupporting
confidence: 65%
“…While extensive roofs make use of solid type growth media to promote plant growth, hydroponic roofs are composed of plastic-planters floating on pure water substrate operating under flood like conditions [55]. The microclimate effects of hydroponic green roofs specifically with respect to rooftop temperature reductions have been measured and modelled using heat balance analyses and programs such as ENVI-met [56,57]. While temperature reductions by hydroponic roofs have been observed, the individual impact of reducing temperature effects over large distances above a single hydroponic roof structure is small [57].…”
Section: Urban Microclimatementioning
confidence: 99%
“…The microclimate effects of hydroponic green roofs specifically with respect to rooftop temperature reductions have been measured and modelled using heat balance analyses and programs such as ENVI-met [56,57]. While temperature reductions by hydroponic roofs have been observed, the individual impact of reducing temperature effects over large distances above a single hydroponic roof structure is small [57]. A comparison of extensive and hydroponic green roofs suggested that hydroponic green roofs are an effective means of reducing roof top temperatures and heat amplitudes and though extensive green roof slightly outperform hydroponic roofs in roof top temperature reductions, the reduced irrigation needs, stormwater storage capability, low maintenance, and superior weed control among other benefits make hydroponic roofs an attractive option with many benefits comparable to wetland roofs [55].…”
Section: Urban Microclimatementioning
confidence: 99%
“…This software has been used in many studies to evaluate, in terms of biometeorological conditions the urban layout (Salata et al 2016) and the influence of the urban greening on micrometeorological variables and outdoor thermal comfort (Lee et al2016;Martins et al2016;Duarte et al2015;Tsilini et al2014, Skelhorn et al2014Müller et al2014;Morakinyo et al2016;Middel et al2015;Ketterer and Matzarakis 2015),while other studies examine green infrastructures on the buildings such as the green roofs (Razzaghmanesh et al 2016;Lobaccaro and Acero, 2015;Sodoudi et al 2014;Peron et al 2015;Song and Park 2015;O'Malley et al 2015;Taleghani et al 2014) and green facades and pergolas (Jänicke et al 2015;Katsoulas et al 2017). In other studies, besides the vegetation, other morphological or topographical features were examined e.g., the changing of outdoor thermal comfort in unshaded courtyards while varying the orientation, height, walls albedo and presence of vegetation (Ghaffarianhoseini et al2015); the influence of urban canyons orientation and aspect ratio on thermal comfort (Ketterer and Matzarakis 2014;Qaid and Ossen 2015); the prevailing residential landscape types and urban forms (Middel et al 2014;Taleghani et al2015), the effects determined by urban density, building height and vegetation (Perini and Magliocco 2014), the variation in the micrometeorological variables in different types of urban textures (Johansson et al 2013), different scenarios in terms of orientation and wind direction (Taleb and Taleb 2014), intervations on the roofs (Wang and Akbari 2014), while the variations in the materials forming the urban texture were also the object studied by Yang and Lin (2016), Kim and al.…”
Section: The Envi-met Microclimate Modelling Systemmentioning
confidence: 99%